Cover Crop Management Practices Rather Than Composition of Cover Crop Mixtures Affect Bacterial Communities in No-Till Agroecosystems - Romdhane, Sana; Spor, Aymé; Busset, Hugues; Falchetto, Laurent; Martin, Juliette; Bizouard, Florian; Bru, David; Breuil, Marie-Christine; Philippot, Laurent; Cordeau, Stéphane (Frontiers in Microbiology, 2019)
Cover cropping plays a key role in the maintenance of arable soil health and the enhancement of agroecosystems services. However, our understanding of how cover crop management impacts soil microbial communities and how these interactions might affect soil nutrient cycling is still limited. Here, we studied the impact of four cover crop mixtures varying in species richness and functional diversity, three cover crop termination strategies (i.e. frost, rolling and glyphosate) and two levels of irrigation at the cover crop sowing on soil nitrogen and carbon dynamics, soil microbial diversity and structure as well as the abundance of total bacteria, archaea and N-cycling microbial guilds. We found that total nitrogen and soil organic carbon were higher when cover crops were killed by frost compared to rolling and glyphosate termination treatments, while cover crop biomass was positively correlated to soil carbon and C:N ratio. Modifications of soil properties due to cover crop management rather than the composition of cover crop mixtures were related to changes in the abundance of ammonia oxidizers and denitrifiers, while there was no effect on the total bacterial abundance. Unravelling the underlyifng processes by which cover crop management shape soil physico-chemical properties and bacterial communities is of importance to help selecting optimized agricultural practices for sustainable farming systems.